914. Implementation and User Experience with a Mobile Stewardship App: Phase One of a Study on Guideline Concordant Prescribing. (15th December 2022) - Thumann, Alexis; Wankum, Michael; Gens, Krista
Abstract: Background: The development of facility-specific antibiotic guides to promote the appropriate use of antibiotics is strongly encouraged; however, the inability to access these resources quickly and easily can be a barrier to optimal antimicrobial prescribing. This study phase aims to determine whether providing guidelines in an easy-to-use mobile app increases access to and awareness of these resources available to providers. Methods: In phase one of this study, our team: migrated facility guidelines over to the Sanford Guide Stewardship Assist TM application, provided education, launched the app (March 14, 2022), and sent out a voluntary pre- and one-month post-implementation REDcap provider survey. Phase two of this study will evaluate antibiotic prescribing for limited indications pre-post app implementation and will include a six-month follow-up survey to assess continued trends in guideline awareness and accessibility. The primary endpoint for phase one is to evaluate the usefulness and effect of the app on provider guideline awareness. Results: As of May 3, 2022, 409 downloads of the app occurred since launch, with the facility-specific antibiogram being the most viewed page. Thirty-five participants completed the pre-implementation survey, and twenty-three completed the one-month follow-up survey. Respondents included medicine residents (54.3%), hospitalists (17.1%), primary care (11.4%), infectious disease (8.6%), internal medicine (5.7%), and others (2.9%). Statistically significant increases pre-post app implementation for strongly agree/agree responses were seen for the statements, "I feel confident in using an antibiogram" (71.4% vs. 95.7%, p=0.02) and "I can easily access our facility-specific antibiotic guidelines when needed" (68.6% vs. 95.7%, p=0.01). At one month, 73.9% and 91.3% of providers agreed with the statements "I would consider myself a better steward of antibiotics because of the app implementation" and "The app is useful to my practice, " respectively. Pre-implementation Survey Responses One-month Post-survey Responses: General One-month Post-survey Responses: App-specific Conclusion: Implementing an antimicrobial stewardship app at a large, non-academic health system promoted accessibility to facility-specific guidelines, reinforced antimicrobial stewardship ideals, and was a valuable resource for prescribers. Disclosures: All Authors : No reported disclosures.